The Influence of Transformational Leadership on Job Performance Mediated by Affective Commitment, Work Engagement, and Self-Efficacy (Case Study: Government Procurement Unit) - Sarah Juliana Manurung; Putri Mega Desiana (Universitas KH. Abdul Chalim Mojokerto, 2025)
Public procurement has become a key sector in achieving a Good Procurement Governance Index. As a strategic unit responsible for procurement in ministries, agencies, and local governments in Indonesia, the Government Procurement Unit (UKPBJ) must optimize leadership to achieve its objectives. This study aims to analyze the influence of transformational leadership on job performance by considering the mediating roles of affective commitment, work engagement, and self-efficacy in the context of UKPBJ in ministries and government agencies in Indonesia. This study employs a quantitative approach with a cross-sectional design. Data were collected through questionnaires involving 232 Civil Servants (ASN) and analyzed using Structural Equation Modeling (SEM) with the assistance of LISREL 8.8 and SPSS 25 software. The results indicate that transformational leadership positively affects employee performance both directly and through the mediating roles of affective commitment, work engagement, and self-efficacy. This research provides practical contributions to human resource management policies in the public sector, particularly in optimizing transformational leadership styles to enhance employee performance. Moreover, this study is expected to serve as a reference for implementing leadership training programs and capacity-building initiatives for ASN in UKPBJ, supporting the success of procurement governance in Indonesia.